2014
DOI: 10.1007/s00426-014-0572-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention and recognition: effects of congruency on episodic learning

Abstract: Recent research on cognitive control has focused on the learning consequences of high selective attention demands in selective attention tasks (e.g., Botvinick, 2007;. The current study extends these ideas by examining the influence of selective attention demands on remembering. In Experiment 1, participants read aloud the red word in a pair of red and green spatially interleaved words. Half of the items were congruent (the interleaved words had the same identity), and the other half were incongruent (the inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
80
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(103 citation statements)
references
References 53 publications
(62 reference statements)
17
80
6
Order By: Relevance
“…An additional contribution that emerges from our data is a possible boundary condition for recent demonstrations of enhanced memory for incongruent attention-attracting stimuli (Krebs et al, 2015;Rosner, D'Angelo, MacLellan, & Milliken, 2015). In these studies, recognition memory for conflict-inducing incongruent stimuli (e.g., a male face on which the incongruent label "FEMALE") was better than recognition memory for congruent or neutral stimuli.…”
Section: The Unique Benefit Of Novelty?supporting
confidence: 54%
“…An additional contribution that emerges from our data is a possible boundary condition for recent demonstrations of enhanced memory for incongruent attention-attracting stimuli (Krebs et al, 2015;Rosner, D'Angelo, MacLellan, & Milliken, 2015). In these studies, recognition memory for conflict-inducing incongruent stimuli (e.g., a male face on which the incongruent label "FEMALE") was better than recognition memory for congruent or neutral stimuli.…”
Section: The Unique Benefit Of Novelty?supporting
confidence: 54%
“…There are two ways in which we could interpret these results: 1) the target receives enhanced attention and therefore it is better encoded or 2) the distractor is suppressed (inhibited) following the selection of the target, so its memory is impaired. However when comparing active and passive conditions, there is no difference in memory for targets, demonstrating that the action does not enhance target processing (Rosner et al, 2014). Instead, distractors in the active condition are less accurately remembered than in the passive one, supporting the inhibitory account (Houghton & Tipper, 1994 However, despite the lack of significant interactions between the active modes (active/passive) and the type of object (target/distractor), we can still observe that, especially in the Where non-episodic measure, there is a trend for selective distractor suppression in the active condition with no change for the target.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed only few studies have looked into the impact of selective attention on episodic encoding, with rather mixed results. Some studies have suggested that actively selected targets receive a boost that increases their encoding in an episodic trace (Rosner et al, 2014;Uncapher & Rugg, 2009;Uncapher & Wagner, 2009). But several others have failed to find such evidence (Christou & Bulthoff, 1999;Plancher et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
AbstractTwo recent studies have reported that incongruent selective attention items are better remembered than congruent items on a surprise recognition memory test (Krebs, Boehler, De Belder, & Egner, 2013;Rosner, D'Angelo, MacLellan, & Milliken, 2014). These findings suggest that an increased need for cognitive control may trigger encoding mechanisms at the time of study that result in better recognition of those items at test, a form of the desirable difficulty effect (Bjork, 1994).
…”
mentioning
confidence: 99%